An educational game to teach numbers in Brazilian Sign Language while having fun. (June 2020) - Pontes, Herleson Paiva; Furlan Duarte, João Batista; Pinheiro, Plácido Rogério
Abstract: This work presents an educational, cross-platform, turn-based, heavily visual-based and touch-ready digital game that targets the learning of signs in BSL for some Natural Numbers by children and adults, called MatLIBRAS Racing . This solution differs from others by having its gameplay based on a cognitive perspective, by promoting the deaf culture in its features as game requirements, by targeting multiple age groups with a single software and by offering a modular software architecture that enables the use of other sign languages besides Brazilian Sign Language (BSL) in the game. An evaluation about educational and gaming features of the game was conducted, focusing its learning potential, gaming components, user experience and social engagement, using as tools surveys, quizzes and observation. The results demonstrated the potential MatLIBRAS Racing as an educational tool, since the majority of its features were rated positively by students, it engaged social relationship among players and helped the learning of signs in BSL, suggesting a promising future for this game in academic environments. Highlights: Learning of the Brazilian Sign Language (BSL) was improved by an educational game. The solution is cross-platform, turn-based, heavily visual-based and touch-ready. Player motivation raised by the entertainment and competition promoted by the game. Cognitive perspective and deaf culture features enhance player experience in gameplay. A modular software architecture enables other sign languages in the game.